In‐capillary reactant mixing for monitoring glycerol kinase kinetics by CE. Issue 13 (10th June 2013) - Nehmé, Hala; Nehmé, Reine; Lafite, Pierre; Routier, Sylvain; Morin, Philippe
<x xml:space="preserve">Abstract</x> CE was used for the first time to study the two‐substrate enzyme glycerol kinase. The capillary was used as a nanoreactor in which the enzyme and its two substrates glycerol and adenosine‐5′‐triphosphate were in‐capillary mixed to realize the enzymatic assay. For kinetic parameters determination, reactants were injected (50 mbar × 5 s) as follows: (i) incubation buffer; (ii) adenosine‐5′‐triphosphate; (iii) enzyme, and (iv) glycerol. Enzymatic reaction was then initiated by mixing the reactants using electrophoretically mediated microanalysis (+20 kV for 6 s) followed by a zero‐potential amplification step of 3 min. Finally, electrophoretic separation was performed; the product adenosine‐5′‐diphosphate was detected at 254 nm and quantified. For enzyme inhibition, an allosteric inhibitor fructose‐1, 6‐bisphosphate plug was injected before the first substrate plug and +20 kV for 8 s was applied for reactant mixing. A simple, economic, and robust CE method was developed for monitoring glycerol kinase activity and inhibition. Only a few tens of nanoliters of reactants were used. The results compared well with those reported in literature. This study indicates, for the first time, that at least four reactant plugs can be in‐capillary mixed using an electrophoretically mediated microanalysis approach.